Natural Hazards Insurance in Europe ? Tailored Responses to Climate Change Needed - Reimund Schwarze; Gert G. Wagner (University of Innsbruck, Department of Public Finance, 2009)
This paper provides an overview on the existing systems of natural hazards insurance in Europe, their structural characteristics and peculiarities. It also discusses the difficulties of an adaptation of these systems to climate change and a growing number of natural disasters. Using the case of Germany as an example, the paper demonstrates that the obstacles facing system change are numerous, including failure to recognise the role of state guarantees in enabling private insurance markets, mistaken legal objections against mandatory insurance, distributional conflicts between central and state governments and re-election considerations by politicians. The adjustments to new weather conditions should reflect existing differences in the regional and national insurance systems in the EU. 'Change in diversity' is seen to offer the best chance to arrive at insurance systems which are prepared for climate change while being adapted to local particularities. Efforts to harmonise national and regional systems as well as top down EU initiatives are rejected in this paper.
Keywords: G22; Q54; 330; Natural Hazards; Insurance; Climate Change; Europe; Germany; Elementarschadenversicherung; Klimaveränderung; Naturkatastrophe; Versicherungstechnisches Risiko; Deutschland; Europa